2020
DOI: 10.54589/aol.33/2/143
|View full text |Cite
|
Sign up to set email alerts
|

Signs of alveolar bone damage in early stages of periodontitis and its prevention by stimulation of cannabinoid receptor 2. Model in rats

Abstract: The aims of the present study were, first, to identify signs of alveolar bone damage in early stages of experimental periodontitis (EP) and, second, to assess its possible prevention by treatment with cannabinoid receptor 2 agonist HU 308. Experimental periodontitis was induced by injections of lipopolysaccharide (LPS) (1mg/ml) in gums surrounding maxillary and mandibular first molar, 3 days per week, and untreated controls were kept for comparison. Then, a 3-week study was conducted including eighteen new rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…Moreover, other related findings showed that HU‐308 has prohomeostasis effects by inducing anti‐inflammatory and osteoprotective properties in oral tissues of rats with LPS‐induced PD (Ossola et al, 2016 ). These studies, along with others (Ossola et al, 2020 ; Zhang et al, 2020 ), highlight the important role of the ECS in oral and systemic health. Moreover, the cytokine and chemokine inhibition profiles of HU‐308 (agonist) and SMM‐189 (inverse agonist) were investigated in activated hPDLFs, and study results showed that CB2R ligands are viable candidates for the development of a new therapeutic intervention for PD (Figure 2 ) (Abidi et al, 2020 ).…”
Section: Synthetic Cannabinoidssupporting
confidence: 60%
“…Moreover, other related findings showed that HU‐308 has prohomeostasis effects by inducing anti‐inflammatory and osteoprotective properties in oral tissues of rats with LPS‐induced PD (Ossola et al, 2016 ). These studies, along with others (Ossola et al, 2020 ; Zhang et al, 2020 ), highlight the important role of the ECS in oral and systemic health. Moreover, the cytokine and chemokine inhibition profiles of HU‐308 (agonist) and SMM‐189 (inverse agonist) were investigated in activated hPDLFs, and study results showed that CB2R ligands are viable candidates for the development of a new therapeutic intervention for PD (Figure 2 ) (Abidi et al, 2020 ).…”
Section: Synthetic Cannabinoidssupporting
confidence: 60%
“…These findings indicate the potential role of CB1 in mesenchymal stem cells and periodontal regeneration, making it a promising target for bone regeneration [105]. In contrast, CB2 activation has been reported to reduce alveolar bone loss in rats with periodontal disease [106]. Additionally, THC in periodontal fibroblasts promotes adhesion and migration, primarily through CB2 activation [88].…”
Section: Regenerative Potential Of Cannabinoids At the Periodontiummentioning
confidence: 96%
“…The presence of both AEA and 2-AG, as other endocannabinoids, with their distinct affinities and receptor interactions, enables the ECS to finely tune cellular responses to maintain homeostasis and adapt to external challenges 13 . The use of phytocannabinoids or synthetic cannabinoids is also a therapeutic possibility in PD treatment under investigation 24,27,30,32,33,37,[40][41][42][43] . Pre-clinical studies have demonstrated that systemic or local application of different cannabinoids (Table 1) might mimic endocannabinoids action and interact with both CB1 and CB2 in periodontitis models in vitro and in vivo 24,33 .…”
Section: Cannabinoids and Periodontitismentioning
confidence: 99%